Catalytic Ozonation Of 2–Hydroxy–1,2,3–Propanetricarboxylic Acid (Jurnal Teknologi (Sciences & Engineering), 2012)
mole ratio of 80. In overall, VZSM5 catalyst could promote the ozonation process better than CuZSM5 and MnZSM5. The results also show that ozone gas with smaller bubble size gave better performance.